The Relationship between Type and Frequency of Online Food Ordering With Obesity in Students of Medan Area University - Laila Apriani Hasanah Harahap; Evawany Aritonang; Zulhaida Lubis (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Online food ordering is a food delivery service through applications that are obtained quickly and safely. This is related to obesity. This type of research uses a descriptive type of study, with a cross sectional study design. This research was conducted at Medan, Medan University with 83 samples taken using purposive sampling method. The data used are primary data obtained based on measurements of student weight and height, recall and food frequency are analyzed by chi- square test. The results of the study showed that there was a correlation between the frequency of online food ordering with obesity (p <0.001) and there was no correlation between the types of food and obesity (p = 0.099) in the students of Medan Area University. To deal with the problem of obesity, it is easy to get access to online food ordering.